The effect of family separation and reunification on the educational success of immigrant children in the United States - T. H. Gindling; Sara Z. Poggio (Institute for the Study of Labor (IZA), 2010)
For many immigrants, especially those from Central America and Mexico, it is common for a mother or father (or both) to migrate to the United States and leave their children behind. Then, after the parent(s) have achieved some degree of stability in the United States, the children follow. Using qualitative and quantitative methods, we examined the hypothesis that separation during migration results in problems at school after re-unification. We find that children separated from parents during migration are more likely to be behind others their age in school and are more likely to drop out of high school.
Keywords: I2; J13; J61; 330; Immigrant children; education; family separation; Migranten; Kinder; Bildungsniveau; Familiensoziologie; Alleinerziehende; USA